2005
DOI: 10.1136/sti.2004.014407
|View full text |Cite
|
Sign up to set email alerts
|

Blind sampling is superior to anoscope guided sampling for screening for anal intraepithelial neoplasia

Abstract: Objectives: Anal cytology smears are either collected ''blind'' (swab inserted 4 cm into anal canal and rotated) or guided through an anoscope (transformation zone visualised and then sampled). We compared these smear techniques with respect to sample quality and patient acceptability. Methods: Using a paired, random sequence clinical trial, 151 homosexual men (n = 95 HIV positive) underwent both smear techniques at a single visit; smear order was randomised and specimens were read blind. Both techniques utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
0
26
1
2
Order By: Relevance
“…In the present study, the material collected for anal cytology was unsatisfactory in 6.2% of smears, a similar percentage to that reported in a study using conventional medium [24] and in another using liquid medium [29]; however, it was higher than the percentages reported in a study on anal cytology in HIV-positive patients [23] and in another on genital neoplasia [30]. …”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In the present study, the material collected for anal cytology was unsatisfactory in 6.2% of smears, a similar percentage to that reported in a study using conventional medium [24] and in another using liquid medium [29]; however, it was higher than the percentages reported in a study on anal cytology in HIV-positive patients [23] and in another on genital neoplasia [30]. …”
Section: Discussioncontrasting
confidence: 51%
“…Although the use of cytology for screening anal lesions is recent, sensitivity and specificity values are similar to those found for cervical cytology. A recent study showed that the technique of blind sampling for anal smears is better than anoscopy-directed sampling, which makes the method even simpler than cervical sampling [29]. Likewise, a cost-benefit analysis showed screening by anal cytology to be a viable option for use within the public healthcare service [41].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical brush and Dacron swabs have been shown to obtain good cellularity and high yield for AIN. 33,34 In our study, factors that could have been related to the elevated number of unsatisfactory results are lack of staff expertise in collecting anal Pap smears since the procedure was newly introduced in the clinic, and also the fact some patients may have had anal intercourse or anal manipulation within 24 h prior to the anal sample collection. Nonetheless, the results underscore the necessity of specialized training of clinicians in performing anal Pap smears and of routinely orienting the patients undergoing anal Pap smear screening to avoid anal intercourse, anal manipulation (with finger insertion or sexual aids), anal enemas or anal douche within 24 h prior to sample collection.…”
Section: Discussionmentioning
confidence: 84%
“…15,19,20,[25][26][27][28] Temos empregado o colposcĂłpio convencional e colhemos material do canal anal para esfregaço, antes de iniciar o exame. Avaliamos o perĂ­neo e a pele perianal dois a trĂȘs minutos depois da aplicação de gaze embebida em ĂĄcido acĂ©tico a 5%, e procuramos por ĂĄreas acetobrancas.…”
unclassified